The Influence of Brand Trust, Brand Reputation, and Brand Relationship Quality on Distributor Loyalty with Distributor Satisfaction of Panen Mas as a Mediating Variable - Mustika Eka Kusuma Wardhani; Damelina Basauli Tambunan (Dinasti International Journal of Education Management And Social Science, 2025)
The gold mining industry in Indonesia has undergone significant changes, particularly with the continuous rise in gold prices, which impacts the distribution of mining products such as water pumps and sand pumps. PT Panen Raya Mustika (Panen Mas) faces challenges in maintaining distributor loyalty amid intense competition. This study aims to analyze the effect of brand trust, brand reputation, and brand relationship quality on distributor loyalty, with distributor satisfaction of Panen Mas as a mediating variable. This is a quantitative study, and data collection was carried out using a questionnaire distributed online via Google Forms to 36 distributors of PT Panen Raya Mustika across various distribution areas. The results show that brand trust, brand reputation, and brand relationship quality significantly affect distributor satisfaction of Panen Mas, which serves as a mediator in enhancing distributor loyalty for Panen Mas.